ANALYSIS OF RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL: HEALTH CALCULATION METHOD AT BANK PERKREDITAN RAKYAT: (Study on PT. BPR Bank Bapas 69 Perseroda Magelang Regency and its Industrial Average in 2018-2020) - Tanaya Pawestri Cita Rinjani (Transpublika Publisher, 2022)
This study aims to determine the level of bank soundness at PT. BPR Bank Bapas 69 (Perseroda) Magelang in 2018-2020 using the RGEC method. Risk Profile containing Net Performing Loan (NPL) and Loan to Deposit Ratio (LDR), Good Corporate Governance, Earnings containing Return On Equity (ROE), Return On Assets (ROA), Net Interest Margin (NIM), and Operating Expenses to Operating Revenue (BOPO), and Capital Adequacy Ratio (CAR) are the RGEC method's used factors. The research methodology is descriptive and employs quantitative techniques. This study utilizes secondary data gathered from PT. BPR Bank Bapas 69 (Perseroda) Magelang's 2018-2020 annual report. The results indicated that PT BPR Bank Fathers 69 (Perseroda) Magelang in 2018 and 2019 had the same percentage value of the composite rating of 95% and the percentage value of the composite rating in 2020 was 92.5%, indicating that PT. BPR Bank Bapas 69 (Perseroda) is in the very healthy category according to the method RGEC.